Temperament and personality: preliminary evidence of possible relationships with multifactorial stress reactivity in healthy adolescents - Ecker, Angelika; Jarvers, Irina; Jacob, Ricarda; Kandsperger, Stephanie; Brunner, Romuald; Schleicher, Daniel (Frontiers in Psychology, 2025)
ObjectiveIt is hypothesized that personality and temperament influence the stress response. However, no study has thoroughly investigated the impact of these factors during adolescence, a critical stage of development and consolidation. In this study, we aimed to explore this relationship, both for personality and temperament aspects, in a sample of adolescents. Therefore, an experimental stress induction, combined with multifactorial stress assessment, incorporating both biological and subjective measures, was conducted.MethodAn acute psychosocial stress reaction was induced in 73 healthy adolescents (11–17 years of age, 63.0% female). Features of the stress response were recorded, including salivary cortisol, salivary alpha-amylase, heart rate, heart rate variability, and subjective stress. We investigated relationships between these factors and control variables (e.g., stress vulnerability and traumatic life experiences), specific trait facets, personality profiles according to the Big Five, and temperament dimensions according to Cloninger.ResultsIn bivariate correlations, salivary cortisol response was negatively associated with Extraversion. Regarding bivariate correlations with temperament, Harm Avoidance was particularly associated with cortisol response and with the subjective stress response. Only stress vulnerability was significantly related to the subjective stress response.ConclusionIn conclusion, the associations between personality/temperament profiles with the stress response are already evident during adolescence, highlighting the developmental aspect and the early emergence of these relationships. These findings suggest that personality and temperament profiles relate to individual differences in adolescent stress sensitivity. Identifying profiles linked to heightened or prolonged stress responses—such as high harm avoidance—may inform early interventions to support at-risk youth.